Controle alternativo da antracnose do feijoeiro com indutores de resistência bióticos e abióticos - Pinto, Renata Riboli (2023)
Anthracnose, caused by the fungus Colletotrichum lindemuthianum (Sacc. & Magnus Lams. – Scrib., is one of the most significant diseases affecting common bean crops. This disease severely impacts productivity and the quality of the final product, leading to the extensive use of chemical products as a primary control method. However, there is an increasing need to explore alternative methods for disease control that combine efficiency with reduced environmental impact and health risks, such as biological control and the use of resistance inducers. To address these issues, this study aimed to evaluate: i) in vitro antagonism of Trichoderma spp. species against C. lindemuthianum races 65 and 77; ii) the efficacy of abiotic inducers and fungicides in in vitro control of C. lindemuthianum races 65 and 77; iii) the response of common bean cultivars to C. lindemuthianum races 65 and 77; iv) the potential of bioproducts and abiotic inducers in controlling anthracnose in common bean. The study comprised in vitro and in vivo experiments conducted in the Phytopathology Laboratory and the agricultural greenhouse at the Federal University of Santa Maria, Frederico Westphalen/RS campus. Three in vitro trials were carried out: the first assessed the antagonistic activity of different Trichoderma species from bioproducts against C. lindemuthianum races 65 and 77 using a direct confrontation technique. The second trial evaluated the antifungal activity of various concentrations of abiotic inducers and fungicides against C. lindemuthianum races 65 and 77. The third trial examined the pathogenicity of races 65 and 77 of C. lindemuthianum on common bean cultivars using the detached leaf technique. In the in vivo trial, an integrated management approach was employed to control anthracnose in common bean cultivar IPR Tuiuiu, caused by C. lindemuthianum race 65, through seed treatment with Trichoderma spp.- based bioproducts and aerial application of abiotic resistance inducers. All Trichoderma isolates exhibited antagonistic effects on the mycelial growth of C. lindemuthianum races 65 and 77 in the direct confrontation test compared to the control. Isolates of T. aesperellum (Quality®) and T. harzianum (Trianum®) showed greater potential for in vitro biological control of the pathogen. The inducers Resistance Bac-F® (RST) and Foskalium 30-20® (FSK), at higher doses tested, demonstrated fungitoxic potential against both races of C. lindemuthianum similar to the fungicide Carbendazim Nortox, while the inducer Estimulus EVO (EST) did not exhibit antimicrobial effects in vitro. Both races of C. lindemuthianum differed in their aggressiveness, leading to varying severities in common bean cultivars, with cultivar IPR Tuiuiu being the most susceptible and cultivars IPR Urutau and IPR Uirapuru showing greater resistance to C. lindemuthianum races 65 and 77, respectively. The combination of control methods such as seed treatment with the bioproducts Trianum® / T. harzianum and Quality® / T. aesperellum, along with aerial application using the abiotic inducer Resistance BAC-F® (RST), proved effective in controlling anthracnose in the bean cultivar susceptible to race 65 IPR Tuiuiu, caused by C. lindemuthianum. This approach also led to the selection of race 65 for inoculation. The abiotic inducer Resistance BAC-F® demonstrated potential as an inducer of resistance to C. lindemuthianum race 65 in common beans, while bioproducts based on Trichoderma spp. did not, when applied individually.